Avaliação do potencial de descarbonização da construção civil com Hidrogênio Verde: Uma análise técnica aplicada ao Maranhão - SILVA, Marcia Delane (2025)
This research aims to assess the potential application of green hydrogen (H2V) as a decarbonization strategy in the industrial segments of the construction sector, with a particular focus on the cement industry in the state of Maranhão, Brazil. The study is based on the recognition that the construction sector is among the largest emitters of greenhouse gases (GHG), and that low-emission technologies such as H2V can play a central role in the transition to a low-carbon economy. The investigation was conducted through a qualitative, exploratory, and descriptive approach, structured in two main phases: a literature review on the use of H2V in industrial processes and a case study applied to a cement plant located in São Luís – MA, which operates exclusively with the grinding of imported clinker. Data were collected through technical visits, interviews with the plant's engineering team, and analysis of operational documents, allowing for the quantification of CO2 emissions and the simulation of mitigation scenarios using H2V. The results show that, even in plants that do not perform local calcination, such as the one studied, the use of H2V can substantially reduce emissions, especially when replacing fossil sources in heat and electricity generation. The substitution of fossil- based electricity and calcination processes can reduce emissions from 975 kg to 590 kg of CO2 per ton of cement. With local clinker production and the use of renewable energy, this reduction can reach up to 91%. These findings position Maranhão as a strategic territory for new sustainable industrial arrangements, supported by its port infrastructure, renewable energy potential, and integration with low-carbon production chains. More than a punctual assessment, the case study is presented as a replicable prototype aligned with ESG principles. The analysis projects real competitive margins for H2V in the state, with cost estimates ranging from US$ 1.5 to 2.5/kg by 2030. It concludes that Maranhão holds strategic conditions such: port infrastructure, renewable energy availability, and favorable logistics, to become a hub for H2V production and application, contributing to the achievement of the Sustainable Development Goals (SDGs) and to economic valorization through carbon credits.